The use of range-resolved interferometry for multi-parameter sensing in a wind tunnel - Barrington, James; James, Stephen W.; Kissinger, Thomas; Staines, Stephen; Prince, Simon A.; Alucsa-Saeza, Erica; Lawson, Nicholas J.; Tatam, Ralph P. (SPIE - International Society for Optics and Photonics, 2023)
The work presented demonstrates that key parameters in aerodynamic structural characterisation of pressure, strain, and structural dynamics, can be all measured via optical fibre sensors interrogated using the principles of range-resolved interferometry (RRI). When used to interrogate sensors simultaneously deployed on a high lift wind in a wind tunnel, the approach yielded resolutions of 31 μPa/ √ Hz and 1 nε/ √ Hz at a bandwidth of 1526 Hz for pressure and strain, respectively, demonstrating the accuracy and versatility of the RRI signal processing technique.
Keywords: Range-resolved interferometry; Wind tunnel; Optical fibre sensors; Strain; Pressure